Pet Ownership and the Complexities of Human-Animal Relationships in Lahore, Pakistan - Ishfaq, Humaira; Haq, Inam Ul (Annals of Human and Social Sciences, 2024)
This research explores the relationship between humans and animals in Lahore, Pakistan, focusing on pet ownership and its impact on animal welfare. The study aims to understand the differences between pet owners and non-pet owners, their interactions with animals, and their thought patterns regarding animal rights. The research uses qualitative methods, including telephone interviews, to explore pet owners’ perspectives and the emotional bonds formed with animal companions. It was found that pet owners care more about their animals’ welfare than non-pet owners or those who have never experienced bonding with animals. However, the study also found that animals in Lahore suffer from mistreatment and neglect, with some pet owners causing death of their pets. The research advocates for increased awareness, stricter animal welfare laws, and a more compassionate society for all creatures, ultimately providing valuable insights and actionable recommendations for improving the lives of animals in Lahore.